Capital Market Reactions Analysis in Energy and Non-Cyclical Consumer Issuers During the Russia-Ukraine War - Richad, Richad; Astawa, I Gede Bratha; Tonggok, Robinson (International Journal Labs, 2023)
Background: Several shares of energy sector issuers rose amid the war between Russia and Ukraine, this is inversely proportional to the Composite Stock Price Index (JCI) which decreased 1.48 percent to 6,817 at the close of Thursday, February 24, 2022. The share prices of several consumer goods issuers that rely on wheat raw materials fell sharply in the past week. Aim: This study aims to analyze whether there is a capital market reaction in energy and consumer non-cylical sector stocks in Indonesia to seven different events related to the war between Russia and Ukraine. Method: Using the event study method, the sample used was 30 issuers, with 15 issuers coming from the energy sector, and 15 other issuers coming from the primary needs sector (consumer non-cyclical). This study obtained secondary data on the list of issuers of energy and primary needs sector stocks on the Composite Stock Price Index, stock prices, daily returns, and trading activity volumes from the website (www.idx.co.id) and (www.finance.yahoo.com). Findings: The market here is efficient in the form of semi-strong, because the capital market reaction is abnormal returns seen within one to two days after the announcement. In addition, the speed at which the market responds to war-related information that will influence the decision to buy or sell stocks is not seen at the beginning of the war. Overall, the market decisions affected by the war were temporary, as evidenced by the absence of significant stock price differences in the recent events studied.